Strategi Kampanye Komersil Untuk Mempromosikan Perawatan Kulit Pemuda Laki-Laki Melalui Merek Kahf - Kinanti Restu Aryani (Penerbit dan Percetakan, CV. Picmotiv, 2025)
Awareness among Indonesian youth regarding proper facial cleansing habits remains relatively low, even though interest in skincare has increased over the past decade. This design project aims to convey messages about skin hygiene to young people by featuring the Kahf Oil and Acne Care product line to encourage a better understanding of skincare among males aged 15–23 years. The methodology employs both qualitative and quantitative approaches, including interviews with experts in communication, design, and skin health, as well as a survey of 112 young male respondents. The campaign, titled KahfBOYS, is designed with communicative visuals, a casual tone of language, and storytelling and illustration approaches that are relevant to the everyday lives of teenage boys. The campaign media are applied across various forms of visual communication to enhance the effectiveness of message delivery. This campaign is expected to build awareness that maintaining skin cleanliness is not merely a temporary trend, but an integral part of a healthy lifestyle, and to eliminate the stigma that skincare is only intended for women